The variation in lateral and longitudinal stress gauge response within an RTM 6 epoxy resin under one-dimensional shock loading - Appleby-Thomas, Gareth J.; Hazell, Paul J.; Stennett, Christopher (Springer, 2009)
The dynamic response of a commercially important epoxy resin (RTM 6) has been studied using plate impact experiments in the impact velocity regime of 80–960 m/s. Both longitudinal and lateral manganin stress gauges were employed to study the development of orthogonal components of stress both during and after shock arrival. In light of recent work raising doubts about the interpretation of lateral gauge data, lateral response within the RTM 6 resin was also used to investigate the physical phenomena being measured by the embedded lateral gauges. US–uP and rX–uP Hugoniot relationships were in good agreement with data for similar polymer materials from the literature. Derivation of shear strength behaviour both during and after shock arrival showed evidence of strengthening behind the shock front, attributed to compression of the cross-linked epoxy resin polymer chains. Comparison of the change in lateral stress behind the shock to the behaviour of an epoxy resin possessing a similar US–uP Hugoniot from the literature showed a different response; likely attributable to enhanced cross-linking present in this second resin. This result suggests that the embedded lateral gauges were, at least in part, measuring a physical response behind the shock within the resin. A Hugoniot elastic limit of 0.88 ± 0.04 GPa was derived and found to be of the same order of magnitude as results found elsewhere for similar materials.
Keywords: shock; hugoniot; resin; epoxy; lateral gauge; diagnostics; RTM6